An accidental journalist the adventures of Edmund Stevens, 1934-1945 - Heckler, Cheryl, 1959- (Columbia : University of Missouri Press, 2007)
'Stevens was the longest-serving American-born correspondent working from within the Soviet Union. In his career, which spanned half a century, he distinguished himself as a war reporter, analyst, and cultural interpreter. Heckler focuses on Stevens's work, especially his reporting for the Christian Science Monitor, and his life from 1934 to 1945'--Provided by publisher.
Description based on print version record.
Includes bibliographical references (p. 281-283) and index.
Keywords: Stevens, Edmund; Journalists -- United States -- Biography; Electronic books